Expression of Sex Hormone Receptor and Immune Response Genes in Peripheral Blood Mononuclear Cells During the Menstrual Cycle - Brundin, Peik M. A.; Landgren, Britt-Marie; Fjällström, Peter; Shamekh, Mohamed M.; Gustafsson, Jan-Åke; Johansson, Anders F.; Nalvarte, Ivan (Frontiers in Endocrinology, 2021)
Sex hormones are known to interact with the immune system on multiple levels but information on the types of sex hormone receptors (SHR) and their expression levels in immune cells is scarce. Estrogen, testosterone and progesterone are all considered to interact with the immune system through their respective cell receptors (ERa and ERb including the splice variant ERb2, AR and PGR). In this study expression levels of SHR genes in peripheral blood mononuclear cells (PBMCs) and cell subsets (CD4+ and CD8+ T-cells, CD56+ NK-cells, CD14+ monocytes and CD19+ B-cells) were analyzed using standard manual qPCR or a qPCR array (TLDA). Nine healthy individuals including men (n = 2), premenopausal (Pre-MP, n = 5) and postmenopausal (post-MP, n = 3) women were sampled for PBMCs which were separated to cell subsets using FACS. Ten Pre-MP women were longitudinally sampled for total PBMCs at different phases of the menstrual cycle. We found that ER was most abundant and, unexpectedly, that ERb2 was the dominant ERb variant in several FACS sorted cell subsets. In total PBMCs, SHR (ERa, ERb1, ERb2, and AR) expression did not fluctuate according to the phase of the menstrual cycle and PGR was not expressed. However, several immune response genes (GATA3, IFNG, IL1B, LTA, NFKB1, PDCD1, STAT3, STAT5A, TBX21, TGFB1, TNFA) were more expressed during the ovulatory and mid-luteal phases. Sex hormone levels did not correlate significantly with gene expression of SHR or immune response genes, but sex hormone-binding globulin (SHBG), a steroid hormone transporting protein, was positively correlated to expression of ERb1 gene. This study provides new insights in the distribution of ERs in immune cells, with ERb2 being the most abundant ERb variant. Furthermore, expression patterns of several immune response genes differ significantly between phases of the menstrual cycle, supporting a role for sex hormones in the immune response.